Inheritance Cultural Values of Local Wisdom Obong Ritual to the Young Generation in Kendal Regency - Arafah, Siti; Atmaja, Hamdan Tri; Arsal, Thriwaty (JESS (Journal of Educational Social Studies), 2023)
The obong ritual is a means of honoring the spirits of the ancestors of the deceased Kalang people. This study aims to analyze the inheritance of cultural values and the perspective of the Kalang people in responding to the implementation of the obong ritual. The research method uses a qualitative approach. Data were taken by in-depth interviews, documentation, and observation. The research was conducted in Tratemulyo Village, Weleri District, Kendal Regency. The results showed that the provision of knowledge was carried out through stories conveyed by parents to their children. The content of the story conveyed contains the importance and meaning contained in the obong ritual for the life of the Kalang community. The inheritance of obong ritual values is carried out by parents as part of efforts to preserve cultural values in the next generation. The inheritance of this value is done to teach the next generation about good and bad or right and wrong, in the hope that the next generation will do it well and right. The views of the Kalang people towards the obong ritual vary, namely as a ritual that must be done and only as a cultural activity.